2019
DOI: 10.1093/jme/tjz200
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Novel Trapping Lures for Monitoring Exotic and Native Container-Inhabiting Aedes spp. (Diptera: Culicidae) Mosquitoes

Abstract: Surveillance for diurnal container-inhabiting mosquitoes such as Aedes albopictus (Skuse), Aedes japonicus japonicus (Theobald), and Aedes triseriatus (Say) have routinely relied on the deployment of multiple trap types, including CO2-baited light traps, gravid traps, oviposition traps, and BG-Sentinel. These trap configurations have met with varying degrees of effectiveness and in many instances likely under-sample these key mosquito vectors. Most recently, the BG-Sentinel trap used in conjunction with the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…(ii) A trapping-lure comparison study (reported by Eastwood et al [10]) was conducted in Stamford, CT In addition, as a pilot study of vertical transmission at those sites, six oviposition cups (black plastic casino cups, lined with seed germination paper), were placed in the eld and checked weekly to collect container-breeding mosquito eggs.…”
Section: Mosquito Collectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…(ii) A trapping-lure comparison study (reported by Eastwood et al [10]) was conducted in Stamford, CT In addition, as a pilot study of vertical transmission at those sites, six oviposition cups (black plastic casino cups, lined with seed germination paper), were placed in the eld and checked weekly to collect container-breeding mosquito eggs.…”
Section: Mosquito Collectionsmentioning
confidence: 99%
“…Adult mosquitoes were identi ed and screened for arbovirus as follows. Pools of up to 50 mosquitoes (grouped by species, location and capture date) are homogenized and inoculated on a Vero (African Green monkey kidney) cell line, for evidence of arboviral infection, as described Eastwood et al [10].…”
Section: Virus Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify viruses, RNA was extracted from isolates using a QIAampViral RNA mini kit (Qiagen, Germantown, MD), eluted in a nal volume of 70 µL. A reverse transcription polymerase chain reaction (RT-PCR) was performed in a 25 µL reaction using a Titan One-Tube RT-PCR system (Roche Diagnostics, Indianapolis, IN) with generic orthobunyavirus primers (10,12).…”
Section: Virus Detectionmentioning
confidence: 99%
“…triseriatus, and thus enhanced chance of detecting LACV if it is present in an area (3); once commercially available, additional baits described Eastwood et al (2020) are even more effective than BG-Lure (10). Minimal eld infection rates reported elsewhere have ranged from 0.26 to 27 per 1,000 mosquitoes tested (15,28,30,31).…”
Section: Entomological Datamentioning
confidence: 99%